THE EFFECTIVENESS OF FORMULATED-MIX OF IPA GLYPHOSATE + METSULFURON METHIL HERBICIDE TO Ageratum conyzoides L. WEED - Hidayat, Topik; ., sarbino (Fakultas Pertanian Universitas Tanjungpura, 2020)
The effectiveness of using herbicides can be improved by using mixed herbicides. The purpose of this study was to study the effectiveness the mixture of a IPA glyphosate + methulfuron methyl with two ratios of 24:1 and 36:1 against Ageratum conyzoides weeds. The study was conducted in Experimental Field Faculty of Agriculture, Tanjungpura University in January - March 2019. The research was arranged in accordance with the Randomized Group Design. Data analysis using probit analysis continued with combination index calculation. The results showed that the combination index of 24: 1 and 36: 1 were 0.84 and 1, respectively, the both ratio of mixed herbicide were not antagonistic to Ageratum conyzoides.Keywords: Ageratum conyzoides, glyphosate, methulfuron methyl, mixed properties